62.9k views
2 votes
Can someone plz simplify this and explain

Can someone plz simplify this and explain-example-1
User Sebtm
by
5.1k points

2 Answers

6 votes

Answer: 10

Explanation:

Equation: (-4)*3*-1*-2

Start from left to right: -4 *3=-12

Go back to the equation: -12*-1*-2

Calculate again: -12*-1= 12

Go back to equation once again: 12-2

Finally, Solve: 10!

I hope this helps!

User Lfxgroove
by
4.9k points
3 votes

Answer:

-24

Explanation:

you can just break it up into
(-4*3)(-1*-2)=-12*2=-24

User TheAddonDepot
by
4.8k points